MESIN PERAJANG SINGKONG BAGI PENGRAJIN KERIPIK SINGKONG SAMBAL DESA PATUMBAK KAMPUNG - Eswanto, E; Razali, M; Siagian, Tony (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2019)
In the process of processing cassava chips, especially chili chips made by the patumbak village community, ranging from stripping, washing, chopping, soaking and packing still use human labor and are done manually with simple tools. So that this problem can be overcome, the solution is to have designed and made cassava chopper machines. The purpose of this PKMS is to help solve the problems faced by small home industries with Appropriate Technology independently in the village patumbak, village. The implementation method begins by examining the technological and equipment deficiencies in the processing of cassava chips, especially the cassava chopper machine. During this time the process of chopping cassava before being fried into chips is done manually. The method used to achieve the PKMS goal is to make a cassava chopper machine in the village of Patumbak. The results obtained are that the PKMS activities have been completed by the team for 1 period of activity, the final result has been obtained the application of appropriate technology in the form of cassava chopper machines in partner villages and partners was greatly helped by these activities. From the activities that have been carried out the last questionnaire score that has been distributed to partner villages is the highest score influencing the results of understanding of the community or partners, where PKMS 2019 partners are satisfied and helped by the existence of the abdimas. The final result that has been obtained is the production of cassava chips increased by 50% when compared to before the team came to do PKMS activities, the condition of this improvement was seen after partners used cassava chopper machines from the PKMS team.